(untitled) (Journal of Medical & Health Sciences Review, 2025)
Aim: The purpose of this study was to compare the diagnostic accuracy of MRI with that of clinical diagnosis in identifying cervical cancer in patients with cervix carcinoma. Methods: This study enrolled 90 participants, ranging in age from 30 to 65, all of whom had a clinical suspicion of cervical cancer. After getting the patient’s signed consent, we took their age, address, socioeconomic situation, co-morbidities, and clinical presentation into careful consideration. In order to detect the cancer, an MRI of the pelvis was conducted on every patient. The gold standard was histopathology. Results: Included patients had mean age 48.76 years. Postmenopausal bleeding was the most common symptom, experienced by 45.6% of patients. Atypical vaginal bleeding was the second most common symptom, seen by 31.1% of patients. Fourteen patients (15.6% of the total) reported a foul-smelling, watery discharge, and seven patients (7.8%) reported pelvic discomfort. The MRI data showed a positive outcome for 72.2% of patients and a poor outcome for 27.8% of patients. Although 23 individuals (or 25.6% of the total) got negative results from histological examinations, 67 patients (74.4%) had favorable results. There was a 93.3 percent success rate for MRI diagnoses. The PPV, sensitivity, and specificity were all above average. Conclusion: We came to the conclusion in this study that magnetic resonance imaging is a useful diagnostic method for the diagnosis of cervical cancer.